Design Thinking In Pharmacy Education: Inspiring Creative Problem Solving in the Next Generation of Pharmacists - Robert Salvatore Pugliese; Gianna Girone (University of Minnesota Libraries Publishing, 2018)
Born from the world of product and service innovation, design thinking is gaining popularity as a method for introducing creative problem solving into the education of health professionals. Mindsets developed through practicing design thinking can help learners and educators address complex healthcare issues in a whole new way. This article aims to introduce the concepts of design thinking to the pharmacy educator, give examples of its use in pharmacy education, and discuss the value of including it in pharmacy education from both an educator and a student's perspective.   Topic: Commentary